The Analysis Study of Association of Obesity and Eczema: A Comprehensive Systematic Review - Christina Hasian Nababan; Martina Marvinova Hutapea; Hotma Pebrina P. N (International Medical Journal Corp. Ltd, 2025)
Background: Eczema is a chronic inflammatory skin condition that impacts 10% of the adult population worldwide, whereas obesity represents a significant global health issue. The relationship between eczema and obesity is intricate and differs among various populations. Mechanisms encompass eczema symptoms, avoidance of physical activity, gut microbiome influences, glucocorticoid medications, and factors related to obesity. Examining the relationship between eczema severity and related factors can guide targeted interventions and enhance comprehension of the shared pathways among these conditions. Methods: This systematic review adhered to PRISMA 2020 guidelines, focusing exclusively on full-text articles published in English between 2014 and 2024. Editorials and review articles without a DOI were excluded to ensure the utilization of high-quality sources. A literature review was conducted utilizing reputable databases including ScienceDirect, PubMed, and SagePub to identify relevant studies. Result: An initial search in databases yielded approximately 600 publications relevant to this topic. After a rigorous three-stage screening process, eight studies that met the inclusion criteria were selected for in-depth analysis. These studies underwent comprehensive critical evaluation, allowing in-depth exploration of the relationship between obesity and eczema. This systematic approach ensures that the analysis is based on high-quality evidence that is consistent with the research objectives. Conclusion: Studies demonstrate a clear correlation between moderate eczema and obesity. No significant association was discovered between severe eczema and high BMI. A higher BMI, comorbidities, and behavior may affect the association. Without a dose-response relationship, a bidirectional relationship is possible. To understand the complex association between eczema and obesity, future studies should investigate a non-linear relationship utilizing BMI as a continuous variable.